Un cierre de fronteras...taxonómico. tepehuanes y tarahumara después de la guerra de los tepehuanes (1616-1631) - Christophe Giudicelli (Nuevo mundo - Mundos Nuevos, 2008)
At the beginning of the seventeenth century, it is clearly impossible to determine with certainty whether the Indians in northwestern New Vizcaya belong to the Tepehuán or Tarahumara nation. All testimonies tend to throw into relief a political and identitary interdigitation. In these early years, the Neovizcayan authorities and the Jesuits paid careful attention to these continuities because the main goal was to expand the missionary province of Tepehuanes.Spanish pacification that followed the Tepehuan war (1616-1619) went beyond a merely military dimension. By defining a guilty nation—Tepehuan—the Spaniards intended to geographically isolate a suspect body. They actually created two discrete entities exclusively defined by their respective positions in the colonial economy of control. This political taxonomical logic was reinforced after Parral's silver mines discovery, and has been misinterpreted in naturalistic terms since the advent of ethnography in the nineteenth century.